Recent Development in the Discovery of Anaplastic Lymphoma Kinase (ALK) Inhibitors for Non-small Cell Lung Cancer - Liu, Jingru; Ma, Shutao (Current Medicinal Chemistry, 2017)
Non-Small Cell Lung Cancer (NSCLC) is an especially aggressive cancer, the optimal drugs for which are still being developed. The anaplastic lymphoma kinase (ALK) is a receptor tyrosine kinase belonging to the insulin receptor superfamily. EML4-ALK fusion gene initially identified in patients with NSCLC in 2007 is defined as a new molecular subset, which is highly sensitive to ALK inhibition. Since the first ALK inhibitor, crizotinib, was approved by the US Food and Drug Administration (FDA) for the treatment of NSCLC patients in 2011, ALK has been identified as a promising target for NSCLC therapy. However, crizotinib is not effective for various point mutations in ALK and central nervous system (CNS) metastasis. To date, there are only eight of second-and third-generation ALK inhibitors in clinical investigation and others are in preclinical research. This review summarizes recent advances of ALK inhibitors, with a focus on their biological activity, selectivity and structure-activity relationship (SAR) information. We hope this review could help medicinal chemists to discover newer ALK-inhibitors to overcome exist issues in the process of drug discovery, such as potency, selectivity and secondary mutations.
Keywords: point mutations